IMPLEMENTATION OF OUTDOOR LEARNING IN THE DEVELOPMENT OF EMOTIONAL INTELLIGENCE IN PRIMARY SCHOOL CHILDREN - Maylan Putra Purnomo; Taqwa Nur Ibad (Adisam Publisher, 2025)
Emotional intelligence is one of the important skills that must be developed in elementary school children. Along with the advancement of educational approaches, outdoor learning has emerged as one of the effective methods in helping children develop aspects of emotional intelligence. In this learning context, children are given the opportunity to interact with the natural environment, peers, and situations that stimulate emotional management and social skills. This article aims to discuss comprehensively how outdoor learning can make a significant contribution to the development of emotional intelligence in elementary school children. With a more natural and practical approach, outdoor learning offers a space to facilitate children's understanding of emotions, stress management, empathy, and collaboration in a more dynamic and enjoyable educational environment.